Growth of Welfare and its Distribution in the U.S., 1979-2013 - Komlos, John (Journal of Income Distribution®, 2019)
In spite of its importance, the growth of welfare and its distribution is an underresearched topic. The usual focus is income, an intermediate product of economic activity, while welfare is the final product. Although results depend crucially on the price index used, it becomes obvious that welfare growth was substantially slower than income growth and that the middle-class quintiles fared worse. The welfare of the top 1% grew three to four times as fast as that of the 3rd quintile. With an interdependent utility function using the 5th quintile as reference, only the top quintile experienced positive welfare gains.